2001
DOI: 10.1084/jem.193.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 Selectively Induces Chemotaxis in T Helper Type 2 Cells, Eosinophils, and Basophils via Seven-Transmembrane Receptor Crth2

Abstract: Prostaglandin (PG)D2, which has long been implicated in allergic diseases, is currently considered to elicit its biological actions through the DP receptor (DP). Involvement of DP in the formation of allergic asthma was recently demonstrated with DP-deficient mice. However, proinflammatory functions of PGD2 cannot be explained by DP alone. We show here that a seven-transmembrane receptor, CRTH2, which is preferentially expressed in T helper type 2 (Th2) cells, eosinophils, and basophils in humans, serves as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

24
921
4
8

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,008 publications
(957 citation statements)
references
References 26 publications
24
921
4
8
Order By: Relevance
“…36: 2401 chemotactic responsiveness to eotaxin and 5-oxo-ETE, while the DP-selective antagonist BWA868c had no effect. Moreover, we found that this PGD 2 effect was specific for eosinophils as compared with neutrophils, since PGD 2 did not alter the responsiveness of neutrophils to 5-oxo-ETE or IL-8, which is in agreement with CRTH2 being expressed in eosinophils and basophils, but not neutrophils [9]. Unexpectedly, PGD 2 even inhibited basophil chemotaxis to 5-oxo-ETE and eotaxin in a ramatroban-sensitive manner, which indicates that the down-stream events following CRTH2 activation in basophils differ fundamentally from eosinophils.…”
supporting
confidence: 85%
“…36: 2401 chemotactic responsiveness to eotaxin and 5-oxo-ETE, while the DP-selective antagonist BWA868c had no effect. Moreover, we found that this PGD 2 effect was specific for eosinophils as compared with neutrophils, since PGD 2 did not alter the responsiveness of neutrophils to 5-oxo-ETE or IL-8, which is in agreement with CRTH2 being expressed in eosinophils and basophils, but not neutrophils [9]. Unexpectedly, PGD 2 even inhibited basophil chemotaxis to 5-oxo-ETE and eotaxin in a ramatroban-sensitive manner, which indicates that the down-stream events following CRTH2 activation in basophils differ fundamentally from eosinophils.…”
supporting
confidence: 85%
“…1 PGD2 is principally produced by activated mast cells and, to a lesser extent, by T helper cell 2 (Th2) cells and dendritic cells 2-4 and exerts its effect through D prostanoid 5 and chemoattractant receptor-homologous molecule receptors expressed onTh2 lymphocytes (CRTH2). 6 A number of recent studies have shown that PGD2 is involved in inflammatory reactions. Mast cell-derived PGD2 suppresses IL-12 production by dendritic cells that induce Th2 responses in vivo.…”
mentioning
confidence: 99%
“…6 A number of recent studies have shown that PGD2 is involved in inflammatory reactions. Mast cell-derived PGD2 suppresses IL-12 production by dendritic cells that induce Th2 responses in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The DP1 receptor is coupled to G s protein and stimulates adenylyl cyclase, leading to increased levels of cyclic adenosine monophosphate (cAMP; Hata and Breyer 2004). A second type of DP receptor [DP2, also referred to as chemoattractant receptor-homologous molecule expressed on T helper cells (CRTH2)] has also been reported, but it has no significant homology with DP1 and has different biological functions and cellular distribution (Hirai et al 2001;Sawyer et al 2002), and some of its signaling is thought to be independent of PGD 2 levels. Furthermore, it has been documented that its activation decreases cAMP and increases intracellular calcium levels (Bohm et al 2004;Sandig et al 2006).…”
mentioning
confidence: 99%